The clinical investigation of the cases diagnosed as Kawasaki disease - 齊藤 景子; 小西 恭子; 岡本 学; 田中 雄二 (The Medical Journal of Matsue City Hospital, 2008)
We analyzed 10 children diagnosed as Kawasaki disease between August 1, 2005 and November 11, 2006.Fifty percent of the patients were resistant to initial high-dose intravenous immunoglobulin（IVIG） treatment.All the patients resistant to IVIG were improved by the additional IVIG treatment. No patient had coronary artery aneurysma. The high rate of the registance might be caused by the deviation of the age or small size of the subject. We compared between resistance and responder : clinical course of illness, laboratory data and symptoms.The resistance visited to our hospital earlier, had high percentage of neutrophilic leukocyte and low serum sodium concentration. The resistance had high platelet count and tended to have low Hb and low serum albumin concentration. We investigated our patients using 4 prediction score which were previously reported. Positive predictive values were 50 to 60％. Negative predictive value was 100％ in Sato’s prediction score. It might be effective to predict the responder.